2008
DOI: 10.1007/s10162-008-0142-y
|View full text |Cite
|
Sign up to set email alerts
|

Encoding Intensity in Ventral Cochlear Nucleus Following Acoustic Trauma: Implications for Loudness Recruitment

Abstract: Loudness recruitment, an abnormally rapid growth of perceived loudness with sound level, is a common symptom of sensorineural hearing loss. Following acoustic trauma, auditory-nerve rate responses are reduced, and rate grows more slowly with sound level, which seems inconsistent with recruitment (Heinz et al., J. Assoc. Res. Otolaryngol. 6:91-105, 2005). However, rate-level functions (RLFs) in the central nervous system may increase in either slope or saturation value following trauma (e.g., Salvi et al., Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 94 publications
6
66
1
1
Order By: Relevance
“…Additional statistical testing confirmed that the post-exposure growth of loudness at high levels did not differ from pre-exposure values (slope = 1, sign test with two tails, MATLAB signtest). The low-level slopes show good agreement with the rate-matching slopes of ventral cochlear nucleus (VCN) chopper units in soundexposed cats (1.73; Cai et al 2009) and the median loudness balance slope from several studies of human recruitment (1.9; Miskolczy-Fodor 1960; Moore and Glasberg 2004;Moore et al 1985;Stillman et al 1993;Zeng and Turner 1991).…”
Section: Growth Of Loudness After Sound Exposuresupporting
confidence: 68%
See 1 more Smart Citation
“…Additional statistical testing confirmed that the post-exposure growth of loudness at high levels did not differ from pre-exposure values (slope = 1, sign test with two tails, MATLAB signtest). The low-level slopes show good agreement with the rate-matching slopes of ventral cochlear nucleus (VCN) chopper units in soundexposed cats (1.73; Cai et al 2009) and the median loudness balance slope from several studies of human recruitment (1.9; Miskolczy-Fodor 1960; Moore and Glasberg 2004;Moore et al 1985;Stillman et al 1993;Zeng and Turner 1991).…”
Section: Growth Of Loudness After Sound Exposuresupporting
confidence: 68%
“…Single-unit studies of the VCN suggest that rate-level functions steepen following sound exposure because of substantial increases in maximum rates (Cai et al 2009). This potential correlate of recruitment is restricted to chopper neurons, which show an average slope of 1.7.…”
Section: Physiological Studies Of Loudness Recruitmentmentioning
confidence: 99%
“…Because different neuron types are uniquely affected by acoustic trauma (Cai et al 2009), hyperactivity may be expressed in one output pathway of the cochlear nuclei, but not another. The dorsal cochlear nucleus (DCN) has received notable attention as a source of tinnitusrelated hyperactivity (Zhang and Kaltenbach 1998;Brozoski et al 2002), although similar patterns of neuropathology have been confirmed in the ventral cochlear nucleus (VCN) (Vogler et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are alternative theories about the underlying cause of loudness recruitment. For example, Heinz et al (2005) and Cai et al (2009) have suggested that changes occur in the auditory system beyond its periphery and that these more central changes are responsible for loudness recruitment. Regardless of its source, loudness recruitment can be examined through measures of loudness (Allen et al, 1990;Hellman and Meiselman, 1993;Buss et al, 1998).…”
Section: Introductionmentioning
confidence: 99%